Exploration of potential lipid biomarkers for age‐induced hair graying by lipidomic analyses of hair shaft roots with follicular tissue attached. (2nd September 2022) - Ma, Yuchen; He, Congfen
Abstract: Background: Age‐induced hair graying (AIHG)is one of the visual hallmarks of aging, but its biological mechanism remains unclear. Changes in the hair‐follicle lipid profiles associated with AIHG have not been defined. Objectives: To define the differences in the hair follicle lipid profiles of female black and gray/white hair follicles. Methods: The lipid profile of hair follicles was determined by ultra‐performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry (UPLC‐QTOF‐MS). Multivariate data analysis was used to determine changes in the lipid profiles in hair follicle roots. Results: We identified the different lipids in hair follicle roots between black hair (HB) and white hair (HW) and analyzed the key lipids that contribute to the development of HW. The results showed that the total lipid content of the HW was significantly reduced. There were significant differences in sphingolipid content, with HB higher than HW. Two subclasses, glucosylceramide (GlcCer) and galactosylceramide, were significantly different. GlcCer, phosphatidylserine, and phosphatidic acid levels were higher in the HB group. The sphingolipid metabolism involved in GlcCer(d18:1/24:1[15Z]) is a statistically significant lipid metabolic pathway. Conclusion: Five major individual lipid candidates are involved in the production of AIHG. GlcCer shows a significant reduction in HW and is a potential target for further research into AIHG.